Understanding IFRS S1 and IFRS S2: a brief overview - Yusoff, Ruslaina; Abd Rahman, Shariful Amran (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Introduction Sustainability reporting is becoming an important issue for every company in communicating information to all stakeholders regarding their involvement in environmental, social and governance practices (Manley, 2024). To gain better standardization and harmonization of reporting, the International Sustainability Standards Board (ISSB) was established in 2021 by IFRS Foundation. The aim is to develop global sustainability disclosure standards. In June 2023, the International Sustainability Standards Board (ISSB) officially released two key standards, IFRS S1, General Requirements for Sustainability Related Financial Information, a framework for companies to disclose sustainability-related risks and opportunities that could impact their financial performance, and IFRS S2, Climate Related Disclosures, which focuses on climate related risks and opportunities. Both IFRS S1 and IFRS S2 promotes consistency, comparability, and reliability in sustainability reporting. Thus, helping stakeholders especially investors in making informed decisions (Deloitte, 2023; MIA, 2023; PwC, 2023; Grant Thornton & MICPA, 2024). These Standards are based on recommendations of the Task Force on Climate-related Financial Disclosures (TCFD).